A revision of the Palaearctic species of Myrmecopora Saulcy, 1864. IV. A new species from Turkey and additional records (Coleoptera: Staphylinidae, Aleocharinae, Falagriini). - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2001)
Myrmecopora (s. str.) ciliciana sp. n. from southern Anatolia, a myrmecophilous species associated with ants of the genus Messor Forel, is described, figured, and distinguished from similar congeners of Myrmecopora s. str. Additional records are presented for several species of Myrmecopora Saulcy, among them the recently described M. (s. str.) wunderlei Assing, whose known area of distribution is mapped.KeywordsColeoptera, Staphylinidae, Aleocharinae, Falagriini, Myrmecopora, Palaearctic region, Turkey, taxonomy, new species, new records, myrmecophily.Nomenclatural Actsciliciana Assing, 2001 (Myrmecopora (Myrmecopora)), spec. n.